Napoleon's hat (thevetia peruviana (pers.) k. schum): new natural indicator acid-base (Research, Society and Development, 2021)
Acid-base natural indicators are dyes extracted from plant parts. These dyes have chromophores in their composition, a substance responsible for color variation as a function of pH. The Napoleon's Hat (Thevetia peruviana (pers.) K. Schum) is a shrubby plant with a woody and lactescent texture. the aim of this study was to evaluate the potential of napoleon's hat (Thevetia peruviana (pers.) K. Schum) as a new natural acid-base indicator and to study the thermal stability behavior of this natural dye. The aqueous extract of napoleon's hat showed excellent color variation as a function of pH in basic medium and in acidic character, it did not show color variation, becoming colorless, thus, it presented similar characteristics to the renowned phenolphthalein indicator. In addition, the natural extract presented excellent thermal stability, not oxidizing during the period under study, becoming an excellent natural acid-base indicator that is easy to acquire and has a low cost to be used in the teaching of Chemistry.